Efektifitas Semu Pelaksanaan UU Nomor 16 Tahun 2019 tentang Perubahan atas UU Nomor 1 Tahun 1974 tentang Perkawinan - Widaryanto, Widaryanto; Syaikhu, Syaikhu; Sukti, Surya (Bulletin of Community Engagement, 2024)
The purpose of this study is to enalysis the effectiveness of the implementation of Law Number 16 of 2019 which amends Law Number 1 of 1974 concerning Marriage. This law revision hopes that the goal of marriage that promotes a happy and sustainable home by the teachings of Islam can be realized. This research uses qualitative methods by conducting field observations. The results showed that increasing the minimum age limit for women in marriage from sixteen years to nineteen, by the changes in Law Number 16 of 2019, brought new legal impacts in society. Although administratively the number of child marriages recorded at the District Religious Affairs Office in West Kotawaringin Regency has decreased, in reality on the ground, unregistered child marriages are increasing. Keywords: Pseudo-Effectiveness of Law, Amendments to Law Number 1 of 1974